2012
DOI: 10.3201/eid1807.120323
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Schmallenberg Virus Antibodies among Dairy Cattle, the Netherlands, Winter 2011–2012

Abstract: Seroprevalence was highest in the eastern part of the country, bordering Germany, where the virus was first identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 17 publications
4
80
0
2
Order By: Relevance
“…carbon dioxide, one of the strongest midge attractants (27). In this study, however, there was no correlation between age of the animal and the presence of antibodies against the SBV, which is in agreement with other studies (6). However, if SBV circulates for a longer period in Poland, the risk of exposure to infection is expected to be higher in older animals.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…carbon dioxide, one of the strongest midge attractants (27). In this study, however, there was no correlation between age of the animal and the presence of antibodies against the SBV, which is in agreement with other studies (6). However, if SBV circulates for a longer period in Poland, the risk of exposure to infection is expected to be higher in older animals.…”
Section: Resultssupporting
confidence: 81%
“…The half-life of SBV antibodies and their ability to neutralise the virus remain uncertain, except for the seropositive cattle, which is resistant to reinfection for at least eight weeks (24). Similarly to other European countries (6,21,25), SBV was able to overwinter in Poland without the active vector. Two possible explanations should be considered including the SBV sylvatic cycle in which the virus is transmitted among the wildlife reservoirs (3,5,13,22), and the survival of the virus in the midge population (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Belgium, a serological survey of 1082 sheep and 142 goats to detect SBV-specific antibodies by ELISA revealed a 98.03% overall between-herd seroprevalence in sheep and a 40.68% within-herd seroprevalence in goats (Meroc et al 2013b). So far, infections with SBV have been detected in Germany, the Netherlands, Belgium, the United Kingdom, France, Italy, Luxembourg, Spain, Denmark, Estonia, Switzerland, Ireland, Northern Ireland, Norway, Sweden, Finland, Poland, Austria, Switzerland and Turkey (Elbers et al 2012;Azkur et al 2013;FLI 2013a;Larska et al 2013;Meroc et al 2013a,b;Sailleau et al 2013). According to unconfirmed reports there could be infection in further European countries.…”
Section: History and Geographic Distributionmentioning
confidence: 99%
“…23,[73][74][75][76][77][78][79][80][81][82][83] Surveys of immune responses among the camelids and ruminants at the Royal Veterinary College, London to the Schmallenberg virus have suggested that although only 3% of ruminants were seropositive in July 2012, whilst 62% had been seroconverted by November 2012 (Brownlie et al, personal communication). 24 The clinical implications and reproductive consequences of this are being studied further.…”
Section: Spreadmentioning
confidence: 99%